Effect of pharmacogenetic markers of vitamin D pathway on deferasirox pharmacokinetics in children. Issue 1 (January 2018) - Allegra, Sarah; Cusato, Jessica; De Francia, Silvia; Longo, Filomena; Pirro, Elisa; Massano, Davide; Piga, Antonio; D'Avolio, Antonio
Abstract : Objectives: Patients with β-thalassemia major have extremely low vitamin D levels, owing to reduced intestinal absorption, subicteric tint, and/or iron-induced higher pigmentation. We investigated whether some polymorphisms within the VDR, CYP24A1, CYP27B1, and GC genes could play a role in deferasirox pharmacokinetics in a cohort of pediatric patients. Patients and methods: Eighteen children with β-thalassemia were enrolled. Drug plasma concentrations at the end of dosing interval ( C trough ) and after 0, 2, 4, 6, and 24 h of drug administration were measured by a HPLC-UV method. Allelic discrimination for VDR ( TaqI, FokI, BsmI, Cdx2, and ApaI ), CYP24A1 ( 22776, 3999 and 8620 ), CYP27B1 ( 2838 and −1260 ), and GC ( 1296 ) single nucleotide polymorphisms was performed by real-time PCR. Results: CYP24A1 8620 AG/GG group negatively predicted C trough in regression analysis ( P =0.012). ApaI AA genotype resulted as a negative predictor of C trough ( P =0.025) and area under the concentration curve ( P =0.007); FoKI CC genotype remained as area under the concentration curve positive predictor ( P =0.008) and TC/CC group as half-life ( t 1/2 ) ( P =0.003) and volume of distribution ( V d ) ( P =0.011) negative one; TaqI TC/CC was retained as a negative predictor of drug maximum concentration ( C max ) ( P =0.004). Moreover, GC 1296 TG/GG seemed able to predict lower time to reach drug maximum concentration ( T max ) ( P =0.033). Conclusion: Our preliminary experience suggested the potential usefulness of vitamin D pharmacogenetic to better understand deferasirox interindividual variability, also in pediatric patients.